PCNA Loaders and Unloaders—One Ring That Rules Them All - Matan Arbel (MDPI AG, 2021)
During each cell duplication, the entirety of the genomic DNA in every cell must be accurately and quickly copied. Given the short time available for the chore, the requirement of many proteins, and the daunting amount of DNA present, DNA replication poses a serious challenge to the cell. A high level of coordination between polymerases and other DNA and chromatin-interacting proteins is vital to complete this task. One of the most important proteins for maintaining such coordination is PCNA. PCNA is a multitasking protein that forms a homotrimeric ring that encircles the DNA. It serves as a processivity factor for DNA polymerases and acts as a landing platform for different proteins interacting with DNA and chromatin. Therefore, PCNA is a signaling hub that influences the rate and accuracy of DNA replication, regulates DNA damage repair, controls chromatin formation during the replication, and the proper segregation of the sister chromatids. With so many essential roles, PCNA recruitment and turnover on the chromatin is of utmost importance. Three different, conserved protein complexes are in charge of loading/unloading PCNA onto DNA. Replication factor C (RFC) is the canonical complex in charge of loading PCNA during the S-phase. The Ctf18 and Elg1 (ATAD5 in mammalian) proteins form complexes similar to RFC, with particular functions in the cell’s nucleus. Here we summarize our current knowledge about the roles of these important factors in yeast and mammals.